Carrying performance and it relationship with some skills for young football players - Mohsen, Mahmoud; Noman, Monzer (Journal of Physical Education, 2014)
This Research Consist of Five Chapters, The Lest Chapter Contain The Definition, The Problem, Aims, Hypothecs And Finally The Riled. The Second Chapter Cantinas KNOW ON Carrying performance and with some skills. The Third Chapter Includes The Research Method And its Field Processes The Researcher Introduced Us To. The Sample Of The Research Which Was Chosen From The College Of Physical Education They First Grade Students And The Smoothing Way In Which They Combined ,The Researcher Also The Field Test, And Also Mentioned The Statistical Method Used In This Research The Fourth Chapter Consist Display and Analyzing Research Results Which Received and Knowing Developing of Basic Skills.Cast The Fifth Chapter Contains Of Conclusions and Recommendation, Also the Research Contains Process For Geostationary And several Attaches an the Paper of Resources.